Knowledge, Attitude and Awareness Towards Research Practice Among Malaysian Premier Polytechnics Academics - Affandi, Haryanti Mohd; Amiruddin, Mohd Hasril; Hassan, Yuhanis Che; Zainudin, Fatin Liyana (Journal of Technical Education and Training, 2015)
Conducting research and implementing its findings is an important ongoing agenda to empower institutions of higher education in Malaysia. Despite ongoing efforts, the number of academics undertaking research activities in the technical and vocational higher education institutions namely, polytechnic education sector remains quite low. This study explored potential factors that may contribute to this situation namely, academics’ levels of research knowledge, awareness, and attitudes towards research practice. A total of 317 of respondents were selected from the engineering and non-engineering academics in three polytechnics; the Sultan Ibrahim Polytechnic, Johor; the Ungku Omar Polytechnic, Perak and the Sultan Salahuddin Abdul Aziz Shah Polytechnic, Selangor. Data were analysed using descriptive and inferential statistical technique for determining average mean scores and differences between means. The data analyses results indicate that academics has high level of research knowledge, positive attitudes and high awareness level towards research practice in the polytechnics. Furthermore, no difference is found between engineering and non-engineering academics. It is concluded that awareness, attitude and knowledge of research practice could not explain the low participations in research practice.